The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1046/j.1464-410x.2001.02038.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different 5‐hydroxytryptamine receptor subtype antagonists on the micturition reflex in rats

Abstract: These findings confirm that only selective 5-HT1A receptor antagonists have favourable effects on the bladder, inducing an increase in bladder capacity with no derangement of bladder contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(125 citation statements)
references
References 28 publications
7
116
2
Order By: Relevance
“…5-HT immunoreactivity has also been associated with bladder recovery (Wrathall and Emch, 2006). Administration of 5-HT agonists facilitates the voiding reflex (Lecci et al, 1992), whereas 5-HT antagonists increase bladder capacity and inhibits the voiding reflex (Testa et al, 1999). The higher numbers of 5-HT-IR fibers in treated rats may thus help explain the drug-induced improvement of bladder function.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT immunoreactivity has also been associated with bladder recovery (Wrathall and Emch, 2006). Administration of 5-HT agonists facilitates the voiding reflex (Lecci et al, 1992), whereas 5-HT antagonists increase bladder capacity and inhibits the voiding reflex (Testa et al, 1999). The higher numbers of 5-HT-IR fibers in treated rats may thus help explain the drug-induced improvement of bladder function.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds targeting the bladder afferent pathway often produce this effect (6,7,17,40). "Shutdown" of bladder rhythmic contraction reflects an increased threshold for induction of contractions and an increased bladder capacity in the conscious cystometrographic study (17).…”
Section: Discussionmentioning
confidence: 99%
“…Thus we did not detect any drug effects of WAY-100635 interacted with 8-OH-DPAT treatment in the present study. Some studies have reported that rhythmic isovolumetric bladder contractions in rats are inhibited by the iv administration of WAY-100635 in a dosedependent manner with a short recovery time of Ͻ20 min (19,31). However, those isovolumetric IVP results have not been based on an examination of the effects of drugs on EUS activity.…”
Section: Effects Of 8-oh-dpat (03 Mg/kg Iv) and Way-100635 (01 Mg/kmentioning
confidence: 99%
“…However, contradictory results have led to various interpretations of these receptor subtype functions in different animal species. Because the rat model has recently been widely used as the main species model for investigating LUT functions, the effects of a 5-HT 1A receptor agonist on LUT functions have been extensively investigated in rats (4,7,11,14,17,19,31).…”
mentioning
confidence: 99%